Microbiological analyses and undergraduate student’s attitudes and perceptions towards microbiological risk of plant-based meat items - Wong, Siew Ching (2023)
Plant-based meat was developed in response to the inefficiencies of meat production when compared to crop harvesting, alongside the increasing public awareness of health-conscious and environmentally friendly dietary choices. Despite its plant-derived nature, the product remained significantly vulnerable to microbial spoilage due to its high moisture and protein levels, as well as its nearly neutral pH. However, the attitudes and perceptions towards the microbiological risks of plant-based meat were not assessed among Malaysian undergraduate students. This study involved the microbiological analyses of plant-based meat items to determine their aerobic colony counts (APC) and yeast and mould counts (YMC) under varying storage temperatures and durations. It was proven that plant-based meat items stored at 4°C exhibited lower microbial load in comparison to those stored at 25°C. As the storage duration increased, a distinct upward trend in the microbial load of plant-based meat items became evident. Therefore, the general public should be aware of the proper storage conditions for plant-based meat items, advocating their storage at 4°C for not longer than 24 hours. The survey regarding attitudes and perceptions obtained a total of 165 responses, revealing a predominant proficiency among Malaysian iii undergraduate students in comprehending and practising measures about the microbiological risks associated with plant-based meat items. In conclusion, plant-based meat items showed a higher level of safety when stored at 4°C for shorter durations, as opposed to storage at 25°C. Furthermore, the study indicated a positive attitude and perception of Malaysian undergraduate students towards the microbiological risks of plant-based meat items